Caracterização físico-química e atividade antioxidante de cogumelos comestíveis Pleurotus djamor (Rumph. ex Fr.) Boedijn cultivados em resíduos agrícolas de folhas de bananeiras e bagaço de cana-de-açúcar - Medeiros, Rossana Lucena de (2023)
Edible mushrooms are fungi visible to the naked eye, multicellular, eukaryotic and heterotrophic. Rich in proteins, carbohydrates, fiber, vitamins and minerals, they have prebiotic, anti-cancer and immunomodulatory action due to the presence of β-glucans. Its consumption is growing and China is the world's largest producer of mushrooms. Brazil produces mushrooms for commercial purposes, and among them are Paris mushrooms, shiitake and shimeji as the most produced. Edible mushrooms can be produced through the use of agricultural waste. The Pleurotos djamor mushroom has an attractive color, low production cost and the ability to grow well in agro-industrial waste. In this sense, the work investigated the effects of substrates originating from agricultural residues, banana leaves and sugarcane bagasse, from the municipality of Areia/PB, on the physical-chemical characterization and antioxidant activity of edible mushrooms P. djamor. These mushrooms were cultivated in 5 (five) treatments with different proportions of agricultural residues for a period of 120 days. The mushrooms were harvested in 3 (three) harvest cycles, and after each cycle, they were dried in a forced air circulation flow oven for 3 (three) days at a temperature of 45 °C. Subsequently, physical-chemical analysis and mycochemical characterization were carried out on the dried mushrooms, analysis of total phenolics and flavonoids, evaluation of the antioxidant activity of the extracts using DPPH and ABTS methods, and NMR-¹H spectral analysis. In general, the substrates produced mushrooms with high protein content (18.77 ± 0.24% to 17.80 ± 0.34%) and dietary fiber (18.02 ± 0.05% to 19.32 ± 0. 39%), low lipid content (0.28 ± 0.08% to 0.04 ± 0.06%) and caloric content with a maximum value of 258.42 ± 8.49, without significant differences between the five treatments (p ≥0.05). Mushrooms also exhibited high levels of phenolics and total flavonoids. Analysis of NMR-¹H spectra indicated an abundant presence of heteropolysaccharides, β-glucans, α-glucans and oligosaccharides, and all mushroom extracts exhibited high antioxidant activity. In this sense, the study demonstrated that mushrooms grow well in agricultural residues with nutritional and functional properties remaining.